2021
DOI: 10.1080/19475705.2021.1973118
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of soil erosion and sediment yield spatio-temporal pattern during 1990–2019

Abstract: Land use/land cover (LULC) change is an important measure to monitor the land degradation. This study focused on the Sebeya watershed located in the western province of Rwanda to evaluate the soil erosion and sediment yield spatio-temporal pattern from 1990 to 2019 occurred due to LULC change. Multi-temporal LULC maps of 1990-2019 and RUSLE model were used to achieve the objectives. The sediment yield was computed as a product of sediment delivery ratio (SDR) and the gross soil erosion. From the period 1990-20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…With respect to modifying factors, the results agreed with Lal (1994), who reported that regardless of rainfall amount, vegetation coverage dissipates the kinetic energy of raindrops. The identical findings of Kulimushi, Choudhari, et al (2021) and Kulimushi, Maniragaba, et al (2021) indicated that under constant conditions of rainfall intensity, poor land use practices and land topography are the most important factors that determine the intensity of runoff and soil erosion. Rainfalls and runoff were highly correlated ( r = 0.79 p < 0.001), but the correlation between runoff and soil erosion was moderate ( r = 0.52 p < 0.001), accordingly, land cover and soil properties got higher relevance, which justified the findings of Nasir and Selvakumar (2018).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…With respect to modifying factors, the results agreed with Lal (1994), who reported that regardless of rainfall amount, vegetation coverage dissipates the kinetic energy of raindrops. The identical findings of Kulimushi, Choudhari, et al (2021) and Kulimushi, Maniragaba, et al (2021) indicated that under constant conditions of rainfall intensity, poor land use practices and land topography are the most important factors that determine the intensity of runoff and soil erosion. Rainfalls and runoff were highly correlated ( r = 0.79 p < 0.001), but the correlation between runoff and soil erosion was moderate ( r = 0.52 p < 0.001), accordingly, land cover and soil properties got higher relevance, which justified the findings of Nasir and Selvakumar (2018).…”
Section: Discussionmentioning
confidence: 58%
“…With respect to modifying factors, the results agreed with Lal (1994), who reported that regardless of rainfall amount, vegetation coverage dissipates the kinetic energy of raindrops. The identical findings of and Kulimushi, Maniragaba, et al (2021) indicated that under constant conditions of rainfall intensity, poor land use practices and land topography are the most important factors that determine the intensity of runoff and soil erosion.…”
Section: Soil Erosion and Runoff In The Eastern Mediterraneanmentioning
confidence: 75%
“…The prioritizing the soil erosion area can be done using the analysing the water holding capacity of soil, compound factor (morohometric, soil character, Geology and land cover), and soil loss rate in Rusle ( Kulimushi et al., 2021 ; Kumar and Singh, 2021 ; Maliqi and Singh, 2019 ). The model identified the soil loss hotspot area for immediate intervention and conservation.…”
Section: Resultsmentioning
confidence: 99%
“…3e was derived from the SRTM 30 m digital elevation model (DEM) (Farr et al 2007) using the spatial analyst slope tool in ArcGIS software. As a readily and freely available DEM product with global coverage, the SRTM DEM has been widely used in many erosion studies (Kulimushi et al 2021b;Senamaw et al 2021), because of its relatively high accuracy compared to other freely available DEM products (Szabó et al 2015).…”
Section: Slopementioning
confidence: 99%